2014
DOI: 10.1111/jon.12185
|View full text |Cite
|
Sign up to set email alerts
|

MRI Texture Analysis and Diffusion Tensor Imaging in Chronic Right Hemisphere Ischemic Stroke

Abstract: In addition to DTI method, TA could assist in revealing the changes caused by infarction, also outside the lesion site. Damaged areas were found more heterogeneous and random in texture compared to unaffected sites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 26 publications
2
7
2
Order By: Relevance
“…To date, research regarding the beneficial role of texture analysis in cerebral infarction is still scarce ( Sikiö et al, 2015 ). Nevertheless, texture analysis was found beneficial in identifying the presence of previous stroke lesions on MR images ( Ortiz-Ramón et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…To date, research regarding the beneficial role of texture analysis in cerebral infarction is still scarce ( Sikiö et al, 2015 ). Nevertheless, texture analysis was found beneficial in identifying the presence of previous stroke lesions on MR images ( Ortiz-Ramón et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Two other studies have investigated the diagnostic value of radiomics in stroke lesions using MR images. Sikio et al [58] evaluated 30 patients with chronic right hemisphere infarction and found that GLCM texture features derived from T2-weighted MR images were capable of revealing changes in both ischemic lesions and the ipsilateral structure outside the lesion (i.e., centrum semiovale). The ischemic region had lower homogeneity texture parameters than the unaffected side, but with relatively high values of complexity and randomness.…”
Section: Diagnosis Of Stroke Lesionsmentioning
confidence: 99%
“…Although texture analysis used images acquired by diagnostic practice, it involves an ensemble of mathematical computations performed with information contained within the images [33]. Texture features extracted from medical images have been demonstrated to provide incremental diagnostic, therapeutic, and prognostic information in many disease entities including various types of cancer [16,17,34], cerebral vascular accident [14,18], liver cirrhosis [35], gastro-intestinal diseases [36], retinal degeneration, and osteoarthritis [37], to list only a few. In heart diseases, texture analysis has been successfully applied to cardiac ultrasonography for myocardial tissue characterization after acute MI [38].…”
Section: Major Findingsmentioning
confidence: 99%
“…On the other hand, among image analysis techniques, texture analysis has been used in many applications of computer vision. Image textures correspond to brightness values and locations of image pixels [14]. Texture analysis provides a vocabulary to represent the image signal intensity or pattern variations [15].…”
mentioning
confidence: 99%